Inside Cover: Conformational SERS Classification of K‐Ras Point Mutations for Cancer Diagnostics (Angew. Chem. Int. Ed. 9/2017). Issue 9 (27th January 2017) - Morla‐Folch, Judit; Gisbert‐Quilis, Patricia; Masetti, Matteo; Garcia‐Rico, Eduardo; Alvarez‐Puebla, Ramon A.; Guerrini, Luca
Abstract : Discrimination of single‐point mutations in large fragments of the K‐Ras gene by an optical approach based on direct surface‐enhanced Raman scattering coupled with chemometrics is presented by R. A. Alvarez‐Puebla, L. Guerrini et al. in their Communication onpage 2381 ff. The unambiguous classification of different mutations provides a potentially useful insight for diagnostics and treatment of cancer.